2020
DOI: 10.3389/fmed.2020.565135
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Chronic Kidney Disease: Still a Challenge

Abstract: Anemia is a clinical feature of chronic kidney disease (CKD). Most common causes are iron and erythropoietin deficiency. The last two decades have yielded significant advances in understanding iron balance's physiology, including iron trafficking and the crosstalk between iron, oxygen, and erythropoiesis. This knowledge sheds new light on the regulation and disturbance of iron homeostasis in CKD and holds the promise for developing new diagnostic and therapeutic tools to improve the management of iron disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…10 Therefore, hepcidin-25 could be a supplement for evaluating functional iron deficiency to conventional iron indices in patients receiving MHD. 22 KNOW-CKD study 23 demonstrated that high hepcidin-25 was associated with anemia in patients with non-dialysis CKD. Serum hepcidin was positively correlated with ferritin but had no relationship with inflammatory cytokines and TSAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Therefore, hepcidin-25 could be a supplement for evaluating functional iron deficiency to conventional iron indices in patients receiving MHD. 22 KNOW-CKD study 23 demonstrated that high hepcidin-25 was associated with anemia in patients with non-dialysis CKD. Serum hepcidin was positively correlated with ferritin but had no relationship with inflammatory cytokines and TSAT.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Therefore, hepcidin-25 could be a supplement for evaluating functional iron deficiency to conventional iron indices in patients receiving MHD. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease Normocytic anemia is a common finding among chronic kidney disease (CKD) patients, mainly due to elevated hepcidin (and reduced iron availability) and decreased EPO levels (98). Increased production of hepcidin is likely secondary to chronic inflammation and decreased renal clearance of this peptide (99). As a result of decreased renal production of EPO, CKD patients generally need erythropoiesis-stimulating agents (ESAs) (99).…”
Section: Iron Therapy For Chronic Diseasesmentioning
confidence: 99%
“…Furthermore, ferric citrate has been proven effective in reducing iv iron and ESA needs, with a good tolerability, in patients undergoing HD [ 131 ]. The liposomal iron represents another example of a new generation of oral iron preparations, which shows high gastrointestinal absorption and high bioavailability [ 132 ]. Compared with other traditional oral iron agents, liposomal iron avoids the direct contact of iron with the intestinal mucosa and bypasses the intestinal hepcidin–ferroportin block via a different uptake mechanism.…”
Section: Iron Supplementationmentioning
confidence: 99%